An ab initio Study of Structural, Electronic and Optical Properties of Janus AlInS2 homo-bilayer - Khengar, S. J.; Parmar, P. R.; Thakor, P. B. (Journal of physics. Conference series, 2023)
By using the first principle calculations, the structural, electronic and optical properties of Janus AlInS2 Bilayer have been calculated. The Janus AlInS2 shows a honey-comb stable structure with semiconducting behaviour having indirect bandgap. The bilayer is found to be energetically favourable. The density of states (DOS) is calculated for Janus AlInS2 Bilayer. It shows absorptions in the visible and ultraviolet regions where prominent peaks of absorption coefficient is found in ultraviolet region of order 105 cm−1. The Janus AlInS2 Bilayer has a high static refractive Index. From the results, it is concluded that Janus AlInS2 Bilayer has a potential application in optoelectronic devices such as coating material to increase reflectivity.